Orígens i influències culturals de la figura de la Dona d'aigua. - SUMOY, JÚLIA ROCAS (Scripta)
The dones d'aigua (water women) are figures of Catalan mythology that have existed since the dawn of time and have evolved and changed over the centuries to become the characters we know today. They present a great multiplicity of forms, names and functions to the different roles they play, always in relation to the local needs of each small society. In this article I intend to carry out a study on their origins and the cultural influences they have received in the different periods of history, from the ancient mythologies to the modern ones, in order to observe the similarities and differences from one culture to another and to understand the role they play in the configuration of a cultural identity.